Diagnosis and Treatment of Constipation and Bladder Contusion Hematuria Due to Trauma in a Cat - Budiono, Novericko Ginger; Dewaruci, Rahmaulana Bayu; Tuliman, Nurul Annisa; Zamrudina, Zahrizada; Fitri, Arni Diana (Jurnal Veteriner; Vol 24 No 3 (2023)DO - 10.19087/jveteriner.2023.24.3.279, 2023)
two-year-old, spayed female, calico, domestic shorthair cat ( Felis catus ) was admitted to IPB University Veterinary Teaching Hospital with a history of hematuria, constipation, and inappetence after being hit by a car. Clinical examination showed pyrexia and the presence of pain when the patient was palpated in the abdomen. Laboratory results showed leukocytosis, lymphocytosis, increased glutamic-oxaloacetic transaminase, increased blood urea nitrogen, proteinuria, overcreatinine, as well as blood and struvite in the urine. The radiographic analysis reported abnormalities in os vertebrae lumbalis I and radiolucent of the colon and rectum. Sonographic findings were cholecystitis, cholelithiasis, nephritis, enteritis, and cystitis. The treatments given were intravenous infusion with normal saline, a single Melovem® injection 0.35 cc, Dulcolax® one 5 mg tablet SID for two days, Samylin® Medium Breed ½ tablet once a day, Cystaid Plus® for cats SID one tab, phytomenadione injection 3 mg/kg SID for two days, Claneksi® syrups 20 mg/kg of body weight per oral BID for five days, Renate® SID per oral for eight days. On the second day of hospitalization, the patient had not pooped, so intra-rectal flushing with physiologic saline was performed, and the patient pooed with normal consistency each day after the enema procedure. Hematuria was observed during the first two days of hospitalization, while no hematuria was observed on the third day. The patient recovered after three days of hospitalization with no hematuria or other abnormal clinical signs or complications. The veterinarian discharged the patient with home treatment with the remaining oral medications.